2008
DOI: 10.1111/j.1600-0714.2008.00638.x
|View full text |Cite
|
Sign up to set email alerts
|

Human laminin‐332 degradation by Candida proteinases

Abstract: Laminin-332 degradation is pH-dependent and differences exist between studied Candida strains. Lm-332 degradation can exert functional disturbances on basement membrane integrity, possibly aiding Candida cell invasion into tissues. Certain synthetic matrix metalloproteinase inhibitors (CMTs, CTT) can inhibit Candida proteinases and may be therapeutically useful in future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 33 publications
(62 reference statements)
1
19
1
1
Order By: Relevance
“…The report of Pärnänen et al. (45) corroborated our results that synthetic serine protease inhibitors reduced the candidal gelatinolytic protease activities and suggested that it may be therapeutically useful in future.…”
Section: Discussionsupporting
confidence: 86%
“…The report of Pärnänen et al. (45) corroborated our results that synthetic serine protease inhibitors reduced the candidal gelatinolytic protease activities and suggested that it may be therapeutically useful in future.…”
Section: Discussionsupporting
confidence: 86%
“…Therefore, enzymatic activity of fungi determines their ability to invade different substances and tissues, including the epidermis and dermis 12 . Candida strains have been found to express both cell‐associated as well as extracellularly secreted proteinases capable of degrading ECM and basement membrane (BM) components, such as collagens, fibronectin, or laminins 13 . Increased proteinase activity is considered to enhance the ability of pathogens to colonise and penetrate host tissues, as well as evade the host’s immune system by degrading a number of proteins important in host defence such as immunoglobulins, complement components and cytokines 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Candidiasis solely caused by C. glabrata has also been reported 1,5 . In a previous study, we observed that some Candida strains have the capacity to degrade human tissue components, such as laminins and fibronectin, which indicate the invasive potential of these Candida species 9,10 . The aforementioned study exemplified the role of C. glabrata as an emerging pathogen.…”
Section: Introductionmentioning
confidence: 90%